Single spike mutation differentiating XBB.1 and XBB.1.5 enhances SARS-CoV-2 cell-to-cell transmission and facilitates serum-mediated enhancement - Criscuolo, Elena; Giuliani, Benedetta; Castelli, Matteo; Cavallaro, Mattia; Sisti, Sofia; Burioni, Roberto; Ferrari, Davide; Mancini, Nicasio; Locatelli, Massimo; Clementi, Nicola (Frontiers in Immunology, 2024)
IntroductionThe ongoing emergence of SARS-CoV-2 variants poses significant challenges to existing therapeutics. The spike (S) glycoprotein is central to both viral entry and cell-to-cell transmission via syncytia formation, a process that confers resistance to neutralizing antibodies. The mechanisms underlying this resistance, particularly in relation to spike-mediated fusion, remain poorly understood.MethodsWe analyzed two clinical SARS-CoV-2 isolates differing by a single amino acid substitution in the S protein. Using biochemical and cell-based assays, we evaluated entry kinetics, syncytia formation, and the neutralizing efficacy of convalescent sera. These parameters were further correlated with S-mediated cell-cell fusion activity.ResultsThe single amino acid substitution significantly altered entry kinetics and enhanced syncytia formation. This modification did not diminished the neutralizing capacity of convalescent sera, but it increased the efficiency of S-induced cell-cell fusion. These findings highlight the mutation’s impact on viral transmissibility and immune evasion.DiscussionOur study demonstrates that even minor changes in the S protein can profoundly influence SARS-CoV-2 transmissibility and resistance to antibody-mediated neutralization. Understanding the molecular basis of S-mediated cell-cell fusion is crucial for anticipating the impact of emerging variants and developing next-generation therapeutic strategies. These insights provide a framework for predicting variant fitness and optimizing treatment approaches against future SARS-CoV-2 variants.